DETEKSI PERBANDINGAN EKSES VOLATILITAS HARGA SERTA REAKSI EARNING TERHADAP RETURN & HARGA SAHAM SEKTOR LQ45 - I. Roni Setyawan; Sudarto , (Universitas Trisakti, 2006)
This paper examines the validity of Efficient Market Hypothesis (EMH) valuation model through stock price volatility and earning volatility excesses. Our research also analyzes stock price reaction to earning. Based on existence of stock price mispricing; there is no investor who will obtain abnormal return if we follow EMH. We find JS is not efficient. Over the observation periods; investors have more concerned with stock market volatility than earning quality. Specifically they have remained to concern about earning quality from LQ 45 companies. Our study provides stock price prediction model that used by investors for decision to buy and to sell. The base for decision of investors is earning. When earning is positive; investors should hold that stock. Otherwise they should release if their earning of stock are negative.Keywords: stock price and earning volatility excesses; mispricing; efficient market,. abnormal return.